2013
DOI: 10.2514/1.j051643
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of a Mach 5.92 Boundary Layer by Two-Dimensional Finite-Height Roughness

Abstract: NOTES are short manuscripts describing new developments or important results of a preliminary nature. These Notes should not exceed 2500 words (where a figure or table counts as 200 words). Following informal review by the Editors, they may be published within a few months of the date of receipt. Style requirements are the same as for regular contributions (see inside back cover).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
23
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 19 publications
3
23
0
1
Order By: Relevance
“…This study found that a series of panels, deformed into the flow, significantly disrupted the unstable growth of disturbances excited in the absence of the deformations. The potential for 2-D wavy walls to stabilize hypersonic boundary layers has also been observed for roughness scale deformations [23][24][25][26][27][28], in which the protuberances alter the local flowfield as opposed to introducing global pressure gradients.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…This study found that a series of panels, deformed into the flow, significantly disrupted the unstable growth of disturbances excited in the absence of the deformations. The potential for 2-D wavy walls to stabilize hypersonic boundary layers has also been observed for roughness scale deformations [23][24][25][26][27][28], in which the protuberances alter the local flowfield as opposed to introducing global pressure gradients.…”
mentioning
confidence: 89%
“…Boundary-layer stability is highly dependent on wall temperature [17,18] and surface geometry [18][19][20][21][22][23][24][25][26][27][28], both of which vary during flight for hot structure hypersonic vehicles. Previous studies have examined how aerothermoelastic effects, such as thermally induced deformations, can augment aerothermal loads [29,30] and impact boundary-layer transition [31,32].…”
mentioning
confidence: 99%
“…However, the corresponding growth mechanism differs from the one active downstream of a three-dimensional roughness investigated by Reshotko & Tumin (2004). Similarly, Duan, Wang & Zhong (2013) found for an adiabatic flat plate at Mach 6 that a two-dimensional wave can be destabilized or stabilized, qualitatively confirming earlier results by Marxen et al (2010). For a cone at Mach 5.85 with an adiabatic wall, Heitmann & Radespiel (2013) found by means of numerical simulations that the disturbance pressure amplitudes for a band of perturbations increase when a roughness element is present, again in accordance with the earlier findings of Marxen et al (2010).…”
mentioning
confidence: 94%
“…(a) (h, k) = (1, 0) case F (-) and case LIN2D (· · ·, -· -) and (b) (h, k) = (1/2, ±1) case LIN3D-S (· · ·, -· -).the roughness on disturbance amplification Marxen et al (2010). varied disturbance frequency with a fixed roughness position, whereasDuan et al (2013) achieved a similar effect by varying the position of the roughness for a fixed frequency.…”
mentioning
confidence: 98%
“…It should be noted that in the last years, the study of the stability of compressible boundary layers has been successful concerning the nonlinear wave interaction [11 15]. It is possible to indicate the results of numerical simulation in applying 2D roughness element for transition control in boundary layer at high supersonic speed [16]. Recent advances of numerical simulation for roughness-induced transition in high supersonic boundary layer are reviewed in [17].…”
Section: Introductionmentioning
confidence: 99%